Evolution, Place and Role of Controlling in a Business Organisation - Sütő, Dávid (International Journal of Engineering and Management Sciences, 2017)
The development of controlling can be traced back to the beginning of 20th century. Thus it has one century of continuous scientific development. Controlling has been applied in fields such as finance, manufactureproduction, and trade sales. In financial accounting different activities have been formed for planning and accounting costs and performance. These activities were integrated by management accounting, which serves the ever growing information needs of the management. In addition to the operational functioning of growing and diversification companies controlling covers even the strategic level. The primary focus of controlling activity at 21st-century businesses is to improve organisational performance. Previously there were differences between the German and Anglo-Saxon trends. According to the German trend controlling is a set of instruments that provides the required information needed for management decision-making and based on it planning, monitoring, and controlling activities could be achieved. Furthermore, the German trend considers that a particular department is responsible for controlling activities. Conversely, according to the Anglo-Saxon conception controlling is considered as a part of management and managers are responsible for efficient allocation of resources, the so-called „management control”, carrying out planning and controlling tasks at the same time. Some differences can be recognised between the two conceptions about where is controlling placed in companies within the organisational framework. However, it can be stated as a fact, that management and controlling are inseparably linked, and the aim of both fields is to increase the performance of a company.